Creole Jews : negotiating community in colonial Suriname - Vink, Wieke (Leiden, The Netherlands : KITLV Press, 2010)
'This study presents a refined analysis of Surinamese-Jewish identifications. The story of the Surinamese Jews is one of a colonial Jewish community that became ever more interwoven with the local environment of Suriname. Ever since their first settlement, Jewish migrants from diverse backgrounds, each with their own narrative of migration and settlement, were faced with challenges brought about by this new environment; a colonial order and, in essence, a race-based slave society. A place, furthermore, that was constantly changing: economically, socially, demographically, politically, and culturally. Against this background, the Jewish community transformed from a migrant community into a settlers' community. Both the Portuguese and High German Jews adopted Paramaribo as their principal place of residence from the late eighteenth century onwards. Radical economic changes - most notably the decline of the Portuguese-Jewish planters' class - not only influenced the economic wealth of the Surinamese Jews as a group, but also had considerable impact on their social statue in Suriname's society. The story of the Surinamese Jews is a prime example of the many ways in which a colonial environment and diasporic connections put their stamp on everyday life and affected the demarcation of community boundaries and group identifications. The Surinamese-Jewish community debated, contested and negotiated the pillars of a Surinamese-Jewish group identity not only among themselves but also with the colonial authorities.'--p. 4 of cover.
Keywords: Jews -- Suriname -- History; Creoles -- Suriname -- History; Suriname -- History